Multiple lines of evidence reveal complex rainbow trout responses to stream habitat enhancements. (9th July 2020) - Collins, Scott F.; Baxter, Colden V.
Abstract: Habitat enhancements seek to ameliorate the detrimental effects of environmental degradation and take many forms, but usually entail structural (e.g. logs, cribs, reefs) or biogenic (e.g. carrion additions, vegetation plantings, fish stocking) augmentations with the intent of increasing fish annual production (i.e. accrual of new fish biomass through time). Whether efforts increase fish production or simply attract fish has long been subject to debate. Streams of the Pacific Northwest are commonly targeted for habitat enhancements to mitigate for the detrimental effects of dams and other forms of habitat degradation on Pacific salmon. Nutrient mitigation (i.e. the practice of artificially fertilising freshwaters) is a form of biogenic habitat enhancement that attempts to mimic the enrichment effects of a natural Pacific salmon spawning event. This approach assumes nutrient augmentations alleviate nutrient limitation of primary producers and/or food limitation of primary and secondary consumers, culminating in increased fish production. We conducted a multi‐year manipulative experiment and tracked responses of interior rainbow trout ( Oncorhynchus mykiss ) to annual additions of Pacific salmon carcasses as part of an effort to enhance the productivity of salmonid populations in streams where salmon runs have been lost. We employed an integrated approach to partition the mechanisms driving numerical responses of trout populations across timescales, to assess population turnover, and to track responses to habitat enhancements across individual to population level metrics. Short‐term numerical increases by trout were shaped by immigration and subsequently via retention of individuals within treatment reaches. As trout moved into treated stream reaches, individuals foraged, grew, and subsequently moved to other locations such that short‐term increases in fish numbers did not persist from year to year. All told, additions of salmon carcasses alleviated apparent food limitation and thereby increased secondary production of rainbow trout. However, at an annual time scale, increased production manifested as larger individual fish, not more fish within treated reaches. Fish movements and high population turnover within treated stream reaches apparently led to the subsequent dispersal of increased fish production. We found multiple lines of evidence that indicated that annual additions of salmon carcasses aggregated rainbow trout and enhanced their annual production. Through this replicated management experiment, we documented dynamic individual and population level responses to a form of stream habitat manipulation across weekly and annual timescales.